Quality of meltwater in terms of potential use in swimming pool facilities - Edyta Kudlek; Anna Lempart-Rapacewicz; Rafał Rapacewicz; Łukasz Lempart; Stanisław Wacławek (Desalination and Water Treatment, 2025)
The changing climate in Europe has led to more areas experiencing water stress. It's important to find ways to use available water resources more efficiently for industrial and recreational purposes. This study aimed to analyze the composition of meltwater collected from various locations in the Silesian Voivodeship in January 2024 to assess its suitability for use in swimming pools. Meltwater samples from a car park, a provincial road, and the roofs of buildings in urban and rural areas were analyzed. The study found that the meltwater contained inorganic pollutants, such as metals and organic micropollutants. Samples from the parking lots and the provincial road showed the presence of polycyclic aromatic hydrocarbons (like benzo(a)pyrene, naphthalene, 4-tert-octylphenol and dibenzo(a,h)anthracene) and substances found in car fluids, including windshield washer fluid. Meltwater collected from the roof surfaces also contained small amounts of polycyclic aromatic hydrocarbons, as well as pentachlorophenol, nonylphenol, and 2,4-dichlorophenoxyacetic acid. Toxicological analysis indicated low toxicity in the samples from both urban and rural roof locations. Similarly, the samples from the parking lot and the provincial road showed low toxicity.